Verbuňk and Rides of the Kings: Reflections on Transformations of Tradition in the Light of Intangible Cultural Heritage - Pavlicová, Martina (Literatura Ludowa. Journal of Folklore and Popular Culture, 2024)
The study of manifestations of folk culture (including those that have survived in modern society) provides a valuable research field for learning about the mechanisms of tradition and its functioning. In addition to the immanent development of tradition, however, it is always necessary to pay attention to external impulses. In the last two decades, the concept of intangible cultural heritage (ICH) certainly belongs to them, as not only is it a theoretical starting point for grasping the study of folk traditions in the present, but it also has a retroactive effect on their form and longevity. The basis of the presented contribution is a reflection on this issue in the Czech environment, particularly concerned with two examples from the region of South-Eastern Moravia: the solo male dance verbuňk, which was entered on Representative List of UNESCO in 2005 (respectively 2008), and the custom “the ride of the kings”, which was entered on the same list in 2011.